The effectiveness of chosen training means in the development of endurance - Cholewa, J.; Czuba, M.; Zajac, A.; Mikolajec, K. (Journal of Human Sport & Exercise, 2009)
The main objective of the work was to present the practical application of a mathematical model to optimize sports training. From empirical data, collected during an experiment a mathematical model of sports training for young swimmers was created. The effectiveness of particular training means on sport results was evaluated. The research was conducted on a group of 20 youth swimmers aged 14±0,5 years, with an average body mass of 50,73±7,39 kg and body height of 164,2±8,12 cm respectively. The swimmers presented a high, national level of sports performance. The research allowed to draw theoretical and practical conclusions regarding the application of the mathematical model in sports training.